Theoretical and Applied Issues of Standardization of the Terms of Prejudicial Inquiry before Handling a Charge Sheet to a Person - T. O. Kuzubova (Bulletin of Kharkiv National University of Internal Affairs)
The latest amendments to the Criminal Procedural Code of Ukraine, which are related to the terms of inquiry before handling a charge sheet to a person, have been studied. The author has carried out the analysis of judicial practice of applying the provisions of the Criminal Procedural Code of Ukraine regulating prolongation of terms of prejudicial inquiry of crimes before handling a charge sheet to a person depending on gravity of a crime and other criteria, which are guided in practice by investigators, prosecutors while determining the urgency of criminal proceedings. The author has compared legal positions of scholars and practitioners, in particular lawyers and prosecutors, on the advantages and disadvantages of establishing clear terms for prejudicial inquiry of crimes before handling a charge sheet to a person. The author has provided the legal assessment of the procedure to cease the criminal proceedings in case of expiration of the terms of prejudicial inquiry before handling a charge sheet to a person. The author has conducted a comparative analysis of the legal consequences of the two general rules of prejudicial inquiry, namely: uncertainty of the terms for prejudicial inquiry of criminal offenses before handling a charge sheet to a person in the Criminal Procedural Code of Ukraine and regulation of clear terms for prejudicial inquiry of crimes before handling a charge sheet to a person in the provisions of the Criminal Procedural Code of Ukraine. The emphasis has been placed on the fact that the specific terms of prejudicial inquiry according to the theory of criminal procedure, are determined in the criminal procedural legislation in accordance with the severity of the criminal offense. At the same time, the author has emphasized that the gravity of the committed criminal offense should not determine the presence or absence of a specific term of prejudicial inquiry in conjunction with all the legal consequences of its clear establishment. The author has distinguished a number of applied issues related to the establishment of clear terms for the prejudicial inquiry of crimes before handling a charge sheet to a person, as well as the application of the rule to cease criminal proceedings in case of their completion. The author has suggested the ways to solve practical problems on the outlined issue, in particular, propositions to exclude destructive provisions from the Criminal Procedural Code of Ukraine, namely provisions setting the terms for prejudicial inquiry of crimes before handling a charge sheet to a person, and related provisions.